Migratory Patterns and Population Redistribution in China’s Zhoushan Archipelago in the Context of Rapid Urbanization - Wenze Yue; Shuangshuang Qiu; Huan Zhang; Jiaguo Qi (Island Studies Journal, 2017)
China’s rapid urbanization has not only resulted in significant economic development but has also introduced various social problems and encouraged human migration. Chinese islands are not immune to these changes. Aspects of island geography and environment mean that island migration has some unique characteristics and underlying drivers. Most recent studies have focused on mainland migration, but few attempts have been made to examine island migration. This paper bridges this gap by focusing on the Zhoushan Archipelago and combines qualitative and quantitative methods to explore the characteristics and causes of migration. The results show that (i) Zhoushan’s population is more concentrated in developed towns and larger islands, (ii) inter-island and island-mainland migrations are the two dominant migration types, and (iii) the main drivers for migration are exhaustion of fishery resources and policy implementation by multi-level governments.